2012
DOI: 10.1017/s0967199411000694
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal methylation of KCNQ1OT1 and differential methylation of H19 imprinting control regions in human ICSI embryos

Abstract: Summary To evaluate the integrity of genomic imprinting in embryos that failed to develop normally following intracytoplasmic sperm injection (ICSI), we analysed the methylation profile of H19 and KCNQ1OT1 imprinting control regions, H19DMR and KvDMR1 respectively, in high-grade blastocysts and in embryos that exhibited developmental anomalies. Significant hypomethylation of KvDMR1 was specifically observed in 5/5 atypical blastocysts graded BC, which probably reflected the vulnerability of the imprint in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 30 publications
(37 reference statements)
6
24
0
Order By: Relevance
“…Interestingly, data in support for such a genome-wide abnormality of DNA methylation in ART pregnancies is scarce, 18,20 as most available studies have focused on specific loci related to imprinted genes. [12][13][14][15][16][17][18][19] Katari et al, 20 using a custom-designed methylation array platform that examined methylation differences in placenta and cord blood samples from ART (N D 10) and naturally conceived (N D 13) pregnancies. The authors analyzed a total of 1,536 CpG sites, most of which were located in the promoters of 736 selected genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, data in support for such a genome-wide abnormality of DNA methylation in ART pregnancies is scarce, 18,20 as most available studies have focused on specific loci related to imprinted genes. [12][13][14][15][16][17][18][19] Katari et al, 20 using a custom-designed methylation array platform that examined methylation differences in placenta and cord blood samples from ART (N D 10) and naturally conceived (N D 13) pregnancies. The authors analyzed a total of 1,536 CpG sites, most of which were located in the promoters of 736 selected genes.…”
Section: Discussionmentioning
confidence: 99%
“…While some of these studies found that ART is associated with abnormal DNA methylation in human gametes, embryos, [12][13][14] placentas, 15 and umbilical cord samples, 16 other studies concluded that this association is not significant. [17][18][19] These apparently conflicting data may be attributed, at least in part, to methodological limitations of some of these studies, such as the inclusion of mixed populations in the study group (e.g., ovulation induction, IVF, and ICSI) and lack of information regarding potential confounders (e.g., indication for ART, treatment protocol, use of cleavage stage embryos vs. blastocysts, and use of frozen vs. fresh embryos).…”
Section: Introductionmentioning
confidence: 99%
“…Whether the observed methylation status of the blastocyst is considered as a normal phenotype for these embryos remains to be answered, but if we consider this phenomenon as a divergence from the norm, numerous explanations can be provided that include: 1) paternally-derived altered methylation [35][36][37] , 2) maternally-derived altered methylation [38] , 3) reduced maintenance of DNA methylation [29,39] , 4) Non-rigid and dynamic methylation statuses of DMR [40][41][42] , 5) reduced or altered methylation due to ART procedure [30,43] , and 6) altered methylation due to technical issues. Each of these propositions requires to be evaluated in the context of new experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The clones with >50% of the CpGs methylated are considered as hyper-methylated, and strands lacked nine or more methylated CpGs were considered to be hypo-methylated [28][29][30] . Using these gauges, the percentage of hyper-methylated clones of H19/IGF2 DMR in the blastocysts was 43.75±5.1%, while this value for the lymphocyte was 50% (Fig.…”
Section: Percentages Of Hyper-methylated Clones Of H19/igf2 Dmrmentioning
confidence: 99%
“…The altered methylation of imprinted genes leads to improper gene dosage during embryonic development and has been associated with several pathologies, including cancers and neurological disorders (Reed and Leff, 1994;Orstavik, 1999;Feinberg, 2004;Demars and Gicquel, 2012;Brioude et al, 2013;McCann et al, 1996;Takai et al, 2001). Recent studies have suggested that assisted reproductive technologies (ARTs), such as superovulation, in vitro fertilisation and embryo culture, favour acquisition of imprinting errors, which can lead to diseases and developmental defects (DeBaun et al, 2003;Gicquel et al, 2003;Maher et al, 2003;Orstavik et al, 2003;Borghol et al, 2006;Bowdin et al, 2007;Khoueiry et al, 2008;Grace and Sinclair, 2009;Chen et al, 2010;Ibala-Romdhane et al, 2011;Khoueiry et al, 2013). During the early stages of embryonic stem cells (ESCs) isolation from pre-implantation stage embryos, embryonic cells are subject to intense in vitro manipulation and environmental changes that may impact the epigenetic status and irreversibly alter the capacity to generate ESC lines or to exhibit the full differentiation potential of genuine ESCs.…”
Section: Introductionmentioning
confidence: 99%